1984
DOI: 10.1021/jf00123a009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidizing and reducing agents on trimethylamine N-oxide demethylase activity in red hake muscle

Abstract: The addition of oxidizing or reducing agents to minced red hake showed that oxidizing agents reduced the rate of dimethylamine (DMA) and formaldehyde (FA) formation, while reducing agents accelerated their formation. To determine the effectiveness of different oxidizing agents, H202, NaOCl, and KBr03 were added at four levels to minced red hake. DMA, FA, and trimethylamine oxide values showed that 0.05,0.10, and 0.25% levels of H202 were most effective in slowing the reaction rate. Although Instron measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Krueger & Fennema (1989) found the inhibition effect of 0.85% (v/v) H 2 O 2 on DMA formation of Alaska pollack ( Theragra chalcogramma ) fillets during frozen storage at −10 °C. Racicot et al. (1984) also reported that the presence of H 2 O 2 in red hake mince at concentration as low as 0.05% (w/w) reduced DMA production during 7 weeks of frozen storage at −12 °C.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Krueger & Fennema (1989) found the inhibition effect of 0.85% (v/v) H 2 O 2 on DMA formation of Alaska pollack ( Theragra chalcogramma ) fillets during frozen storage at −10 °C. Racicot et al. (1984) also reported that the presence of H 2 O 2 in red hake mince at concentration as low as 0.05% (w/w) reduced DMA production during 7 weeks of frozen storage at −12 °C.…”
Section: Resultsmentioning
confidence: 91%
“…(1984) also reported that the presence of H 2 O 2 in red hake mince at concentration as low as 0.05% (w/w) reduced DMA production during 7 weeks of frozen storage at −12 °C. H 2 O 2 is thought to create oxidising conditions in the fish muscle and affect the reducing conditions necessary for TMAOase activity (Parkin & Hultin, 1982; Racicot et al. , 1984).…”
Section: Resultsmentioning
confidence: 99%
“…As the gadoid fishes play an important role in this industry there is a need for studying practical pretreatments which could prevent the production of DMA and FA in these products during frozen storage. Several attempts have already been made: removal of TMAO and soluble proteins by washing the minces, addition of oxidizing agents and packaging in oxygen permeable materials (Landolt & Hultin, 1981 ;Reece, 1983;Racicot et al, 1984). Heat treatments have also D .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hypotaurine and taurine were active in the absence of cations (Spinelli and Koury 1981). Oxidants and Cu2+ were found to inhibit the decomposition of TMAO (Racicot et al 1984).…”
Section: Introductionmentioning
confidence: 95%